GCSE Physics - "Duncan, Tom" (,Oxford press london)
Reflecting the revised GCSE specifications, this fourth edition includes additional material on the uses and dangers of radioactivity, sections on communication and the technological applications of physics such as ultrasonic techniques
Keywords: Physics - Textbook